Health-related quality of life and psychosocial outcomes in long-term survivors treated with immune checkpoint inhibitors: a nationwide multicenter study - Sahin, Taha Koray; Atalah, Fatih; Koylu, Bahadir; Oruc, Ahmet; Acarbay, Aydin; Karakok, Akgun; Dogan, Sevgi; Kikili, Cevat Ilteris; Turhan, Görkem; Emin, Gamze; Celik, Selahattin; Deliktas Onur, Ilknur; et al. (Frontiers in Immunology, 2025)
BackgroundThe increasing use of immune checkpoint inhibitors (ICIs) has resulted in a growing population of long-term survivors (LTS). However, the long-term psychosocial and quality of life (QoL) outcomes in these patients remain underexplored. This study aimed to evaluate QoL, psychological morbidity, fear of cancer progression (FoP), and functional outcomes in cancer patients treated with ICIs for at least six months without disease progression.MethodsThis cross-sectional, multicenter study included 346 adult cancer patients from 17 tertiary oncology centers in Türkiye. Participants had received ICIs for ≥6 months in (neo)adjuvant or metastatic settings. Standardized questionnaires assessed QoL, psychological distress, FoP, immune-related adverse events (irAEs), and work status.ResultsThe median age of the cohort was 62 years (IQR: 53–69). Average survivor QoL was comparable to the Turkish general population; but 119 (34.5%) survivors had poor QoL. Clinically relevant symptoms of depression and anxiety were present in 24.3% and 20.8% of patients, respectively, while 48% reported FoP. The overall return-to-work rate among patients initially employed was 50.9%, with 72.7% returning within the first year. Depression, anxiety, and FoP were negatively correlated with all QoL domains. All grade irAEs were common (53.8%) but not significantly associated with worse QoL (p=0.149).ConclusionsThis study represents one of the largest cohorts to date evaluating survivorship issues among LTS treated with ICIs. Among patients receiving ICIs for at least six months, nearly one-third experienced impaired QoL, primarily driven by psychological distress and FoP. Further research is needed to address survivorship care in this population.